Business vocabulary in use : - Mascull, Bill (Cambridge University Press, 2002)
This is a self-study reference and practice book for upper intermediate and advanced learners of English who need vocabulary for business and professional purposes. Business Vocabulary in Use Advanced is a new self-study reference and practice book for advanced learners of English who need vocabulary for business and professional purposes. The book has been carefully researched using the Cambridge International Corpus to ensure that the 2,000 new words and expressions represent the English that native speakers actually use. The book consists of 50 units and follows the highly successful format of the English Vocabulary in use range with presenationa maerial on the lfeft-hand page and practice exercises on the right hand page. The book covers a wide variety of up-to-date business topics and concepts.